Air pollution nanoparticle exposure reduces neurotrophin signaling and causes hippocampal neural stem cell quiescence in mouse brain. (20th December 2022) - Zhang, Hongqiao; Zhang, Nathan; Li, Andrew; Diaz, Arnold; Shkirkova, Kristina; Ge, Brandon; Florentino, Abigail; Sioutas, Constantinos; Mack, William J; Bonaguidi, Michael Anthony; Finch, Caleb E
Abstract: Background: Exposure to urban air pollution particles is strongly associated with higher risks of accelerated cognitive decline, cerebral atrophy, and dementia in multiple population studies. Among possible mechanisms is the decrease of neurotrophins, shown for BDNF in human exposures, which have critical roles in regulating adult neurogenesis and synaptic plasticity. Method: C57BL/6 mice were exposed to nano‐sized particulate matter (nPM, batch nPM2016a) from urban traffic air pollution for 8 weeks and the mRNAs of neurotrophins and receptors in mouse brain were measured by qPCR assay and neural stem cells measured by immunohistochemistry. Result: nPM exposure altered mRNA levels of neurotrophin genes ( Ngf, Bdnf, Ntf‐3 and Ntf‐4/5 ) with brain region‐specificity. In cerebral cortex (CX), Ngf and Ntf‐3 were decreased (17% and 29% respectively), Ntf‐4/5 increased (78%), and Bdnf unchanged. In hippocampus (HP), Bdnf and Ntf‐4/5 were decreased (40% and 38% respectively) while Ngf and NTF‐3 unchanged. In olfactory bulb (OB), only Bdnf was decreased (10%). The mRNAs of neurotrophin receptors ( Trka, Trkb, Trkc and p75Ntr ) in CX, HP and OB were less responsive to nPM exposure, and only shown by OB with 22% decrease of p75Ntr and 14% decrease of Vgr (VGF nerve growth factor inducible). Exposure to nPM increased the quiescence of neural stem cells in hippocampal SGZ by IHC assay (Control 69.3% VS nPM 76.6%, P = 0.02), but did not alter the total number of neural stem cells. . Conclusion: Chronic air pollution exposure altered neurotrophin signaling with factor‐ and brain region‐specificity, and increased neural stem cell quiescence.